Hybrid palm oil mills maintenance system - Hasan Basari, Abd Samad; Herman, Nanna Suryana; Desa, Mohammad Ishak (Penerbit Universiti Teknikal Malaysia Melaka, 2009)
This paper proposes a technique that enhances snapshot model for cause of failure and decision analysis in order to easily assist maintenance engineers during identification and definition of the actual maintenance problem. The technique is a hybrid of failure mode, effect and criticality analysis, information technology and decision analysis into the snapshot model. A tool that automates the hybrid of snapshot modelling for cause of failure and decision analysis is also developed. This tool aims to ensure maintenance engineers can conduct snapshot modelling with little or without the help of operation research experts to facilitate in the cause of failure and decision analysis process.